Female flowers first: QTL mapping in eastern black walnut (Juglans nigra L.) identifies a dominant locus for heterodichogamy syntenic with that in Persian walnut (J. regia L.) - Warren Chatwin; Devin Shirley; Jacqueline Lopez; Joseph Sarro; John Carlson; Alison Devault; Mike Pfrender; Ronald Revord; Mark Coggeshall; Jeanne Romero-Severson (Tree Genetics & Genomes, 2023)
Eastern black walnut ( Juglans nigra L.), one of the most valuable timber and veneer trees in North America, provides nut shells with unique industrial uses and nut kernels with distinctive culinary attributes. A mature F 1 full-sib progeny orchard of 248 individuals from the cross of two eastern black walnut cultivars provides a long-term resource for discovering genetic mechanisms controlling life history, quality traits, and stress resistance. The genetic linkage map, constructed with 356 single nucleotide polymorphism (SNP) markers and 62 expressed sequence tag simple sequence repeats (EST-SSRs), is 1645.7 cM in length, distributed across the expected 16 linkage groups. In this first application of QTL mapping in J. nigra , we report QTL for budbreak, peak pistillate bloom, peak staminate bloom, and heterodichogamy. A dominant major QTL for heterodichogamy is reported, the sequence for which is syntenic with the heterodichogamy QTL on chromosome 11 of Persian walnut ( J. regia L.). The mapping population parents are both protogynous, and segregation suggests a Mendelian component, with a 3:1-like inheritance pattern from heterozygous parents. Mapping the sequenced EST-SSR markers to the J. regia “Chandler” V2.0 genome sequence revealed evidence for collinearity and structural changes on two of the sixteen chromosomes. The inclusion of sequenced EST-SSR markers enables the direct comparison of this and subsequent J. nigra maps and other Juglandaceae genetic maps. This investigation initiates long-term QTL detection studies for quality and stress resistance traits in black walnut.